The settlement structure-related characteristics and social processes of Hajdúböszörmény after the millennium - Mező, Barna (Acta Agraria Debreceniensis, 2012)
The spatial structural position of Hajdúböszörmény (ease of access) and its economic and social endowments which are more favourable than those of its surroundings make the town more desirable as a target of migration. These endowments are rather advantageous on their own, but the specific settlement structure of the town results in the fact that concentrated, unmanageable and majorly segregated social crisis points have developed in some easily circumscribable parts of the settlement which could lead to a social explosion.